Aspects of Career Management and Success in Educational Organizations - CHIRIMBU, Sebastian Cristian (Annals of Spiru Haret University. Economic Series, 2022)
A modern educational institution should create the necessary conditions for the integration and development of the personal and professional competences of the teachers in order to obtain a successful career. In the current context of the educational system in the Republic of Moldova and Romania, the capitalization of human resources is a priority objective of the managers of educational institutions. The difficulties they face, the constantly changing educational reforms, the unpredictable and challenging situations are known partially or impartially theoretically and practically by teachers who are beginning to integrate into the institution, and the process of insertion from educational institutions is often not effective. We will analyse the characteristics of a successful career but also the motivation for achievement as an important component of the professionalization process, teachers thus tending to pursue challenging careers, complex enough, but not so difficult as to end in failure. Therefore, if professional motivation is an important endeavor, because it starts from the idea that a large part of everyone’s life spends at work, performance denotes the achievement and ability of the teacher to respond to tasks and to be a model for those in the organization when it comes to involvement and responsibility.